2002
DOI: 10.1536/jhj.43.187
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Artery Occlusion Following Cardiac Catheterization.

Abstract: SUMMARYWe describe a 66-year-old Japanese man in whom central retinal artery occlusion followed cardiac catheterization. After the procedure, blurred vision was noted in the right eye, and ophthalmological examination revealed an occlusion. Central retinal artery occlusion is a very rare but serious complication of cardiac catheterization. We should anticipate this potential risk to ensure prompt detection and treatment. (Jpn Heart J 2002; 43: 187-192)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…An experimental study of central retinal artery occlusion showed that occlusion lasting about 97 min resulted in massive, irreversible damage. Thus, no treatment instituted much longer than 1.5 hours after the onset can be expected to restore vision [19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…An experimental study of central retinal artery occlusion showed that occlusion lasting about 97 min resulted in massive, irreversible damage. Thus, no treatment instituted much longer than 1.5 hours after the onset can be expected to restore vision [19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…The causes of CRAO include embolism, thrombosis, vasculitis, arterial spasm, arterial dissection, and hypertensive arteriolar necrosis [3]. Of these, embolism is by far the most common cause, and the major source of emboli is a plaque in the carotid artery [10].…”
Section: Discussionmentioning
confidence: 99%
“…For example, less than one hundred cases of stroke from chiropractic manipulation have been reported since 1925 [1,2]. Five cases of central retinal artery occlusion following cardiac catheterization [3,4] and one case of central retinal artery occlusion after chiropractic manipulation on the neck have also been described [1]. Here we describe a patient with central retinal artery occlusion following chiropractic manipulation, which has not previously been reported in Korea.…”
mentioning
confidence: 85%
“…An experimental study on central retinal artery occlusion showed that occlusion lasting about 97 min resulted in massive, irreversible damage. Thus, no treatment instituted much longer than 1.5 hours after the onset can be expected to restorevision 16,17 .…”
Section: Introductionmentioning
confidence: 99%